A4.06 Mobilisation of joint-resident mesenchymal stromal cells for articular cartilage regeneration. (24th February 2016) - Khalil-Khan, A; Baboolal, T; Wall, O; Jones, E; McGonagle, D
Abstract : Background and objectives: Microfracture is a recognised procedure used to treat isolated cartilage injuries or defects, in which bone marrow mesenchymal stromal cells (BM-MSCs) are thought to migrate into the created blood clot, leading to subsequent cartilage repair via fibrocartilage formation. The discovery of MSCs in the synovium 1 and synovial fluid (SF) 2 provides a potential mechanism for repairing cartilage'from the top down' via their migration and homing to the microfracture site, however SF-MSCs are usually lost with joint irrigation. The purpose of this work was threefold; first to test the hypothesis that SF-MSCs can be replaced, and also their numbers further increased by synovial mechanical agitation, second that these cells were capable of rapid adhesion to clots and third that the clot composition influenced MSC migration. Materials and methods: Ex-vivo mechanical agitation of the human superficial synovium and in vivo intraoperative agitation of the synovium of patients undergoing arthroscopy were performed with the use of cytology brush. Colony-forming unit-fibroblast (CFU-F) assay was performed to quantify released MSCs. Adhesion to clots was studied by comparing Platelet Rich Plasma (PRP), Whole Blood (WB) and White clots (WC). Migration studies were performed using passage 2/4 synovial MSCs in trans-well migration assay. MSC migration was compared between PRP and pooled human Platelet Lysate (hPL). Results: Ex-vivo agitating of the synovium compared to irrigation alone increased MSC number 2.7-fold (n = 10, p = 0.002). Intraoperative arthroscopic agitation of the synovium replaced SF-MSCs (lost following irrigation), resulting in a 6-fold increase over irrigation alone (n = 9, p = 0.002). Released synovial MSC adhesion to clots was observed within 30 min with no difference between clot compositions. Released synovial MSCs demonstrated a trend for a better migration towards hPL compared to PRP. Conclusions: Synovial MSCs can be released by mechanical means in vivo and these cells were capable of migration and rapid adherence to a relevant biological scaffold. Thus providing a rationale for one stage MSC augmentation by synovial brushing in combination with microfracture, as a strategy for cost effective joint repair. References: De Bari, et al . Arthritis Rheum. 2001 Jones et al. Arthritis Rheum. 2004